Management of subcondylar mandible fractures in the adult patient - Hackenberg, Berit; Lee, Cameron; Caterson, Edward J. (The journal of craniofacial surgery, 2014)
The treatment of subcondylar mandible fractures is a topic of debate and can be variable even though these fractures are commonly seen. Historically, the treatment algorithm was between open reduction and closed treatment. Now, recent technical advances regarding the use of the endoscope in the field of craniofacial surgery provide additional treatment options. This article aimed to evaluate 3 current management strategies: closed reduction with maxillomandibular fixation, open reduction with internal fixation, and endoscopic-assisted reduction with internal fixation. We present our rationale for surgical decision making and attempt to develop an algorithmic approach to subcondylar fractures. - Ankylosis of the temporomandibular joint is a feared complication in these fractures that can lead to the decision to apply maxillomandibular fixation for potentially too short of a period. It is the condylar head fractures within the joint's capsule that contain the hemarthrosis that are often responsible for ankylosis. Subcondylar fractures are, by definition, below the attachment of the joint capsule and in general are devoid of ankylosis. Therefore, maxillomandibular fixation is recommended to be applied for a period of 4 to 6 weeks in most cases. Open reduction with internal fixation can increase the risk for facial nerve damage during the operative approach. However, open reduction is often necessary in fracture patterns with a high degree of displacement. In these cases, facial nerve monitoring can successfully mitigate risks to allow safe exposure for open reduction with internal fixation of subcondylar fractures. Endoscopic-assisted reduction with internal fixation combines the benefits of both techniques while minimizing their associated risks. Nevertheless, reduction can be difficult especially when there is significant medial displacement of the proximal fracture fragment. In our experience, the endoscopic option is optimal for mildly displaced fractures and for the patient with multiple injuries who cannot tolerate closed reduction.